Patient and practitioner priorities and concerns about primary healthcare interactions for osteoarthritis: A meta-ethnography. Issue 7 (July 2022) - Vennik, Jane; Hughes, Stephanie; Smith, Kirsten A.; Misurya, Pranati; Bostock, Jennifer; Howick, Jeremy; Mallen, Christian; Little, Paul; Ratnapalan, Mohana; Lyness, Emily; Dambha-Miller, Hajira; Morrison, Leanne; et al.
Highlights: Healthcare interactions for OA are often based on discordant priorities and concerns. A shared understanding can be fostered through open dialogue and validating the patient experience. Clear non-medical language and sharing tailored information promotes mutual trust and respect. Greater working in partnership between patients and practitioners can help build shared goals for management. Abstract: Objective: To explore primary care practitioners' (PCPs) and patients' priorities and concerns for healthcare interactions for osteoarthritis (OA) in primary care. Methods: We searched Embase, CINAHL, Medline, PsychInfo (1990 to present) for primary qualitative and mixed methods studies with findings concerning healthcare interactions for OA symptoms. Patient and PCP perceptions were analysed separately then inter-related using a 'line of argument' synthesis. Results: Twenty-six studies reporting qualitative data from 557 patients and 199 PCPs were synthesised. Our findings suggest that therapeutic interactions for OA can be based on discordant priorities and concerns; some patients perceive that PCPs hold negative attitudes about OA and feel their concerns about impact are not appreciated; some PCPs feel patients have misconceptions about prognosis, and hold pessimistic views about outcomes; and both tend to de-prioritise OA within consultations. Conclusion: Greater working in partnership could build mutual trust, facilitate tailored provision of information, and foster a shared understanding of OA upon which to build realistic goals for management. Practice implications: Developing a better shared understanding of OA has the potential to improve the quality of healthcare interactions for both patients and PCPs. The significant impact of OA on everyday life means it should be given higher priority in primary care consultations.